Endoscopic retrograde cholangiopancreatography in diagnosis and treatment of primary sclerosing cholangitis - Gotthardt, Daniel; Stiehl, Adolf (Clinics in liver disease, 2010)
Primary sclerosing cholangitis is characterized by progressive fibrosing obliteration of the biliary tract. In some cases the disease is restricted to the small bile ducts, but most patients develop fibrotic stenoses of the larger bile ducts. Despite advances in magnetic resonance cholangiography, in unclear cases endoscopic retrograde cholangiography is necessary to make the correct diagnosis. In patients with total or subtotal strictures of the large bile ducts, these so-called dominant stenoses may be treated by endoscopic balloon dilatation and/or stent placement, though in the large majority of cases a stent placement is not necessary. Several studies showed an improvement of biochemical parameters after endoscopic treatment, and actuarial survival in these patients was improved compared with predicted survival. Endoscopic retrograde cholangiography allows tissue sampling, brush cytology, and bile analysis for early detection of cholangiocarcinoma, a major complication of primary sclerosing cholangitis. Despite successful endoscopic opening of bile duct stenoses, patients often progress to liver failure, leading to liver transplantation as the treatment of choice.
Gesehen am 27.04.2023